Modeling Academic Motivation Based on Academic Buoyancy and Academic Conscientiousness Mediated by Teacher–Student Relationship Quality in Secondary School Students of Zahedan - Alisofi, Allah Nazar (International Journal of Education and Cognitive Sciences, 2025)
Purpose: The objective of this study was to model academic motivation in secondary school students based on academic buoyancy and academic conscientiousness, considering the mediating role of teacher–student relationship quality. Methods and Materials: This descriptive correlational study was conducted among 400 secondary school students in Zahedan, selected through stratified random sampling based on Morgan and Krejcie’s sample size table. Four standardized questionnaires were used to measure academic motivation, academic buoyancy, academic conscientiousness, and teacher–student relationship quality. Descriptive statistics and Pearson correlation coefficients were calculated using SPSS-27, and Structural Equation Modeling (SEM) was conducted using AMOS-21 to test the hypothesized model. Findings: The results indicated that both academic buoyancy (β = 0.29, p < .001) and academic conscientiousness (β = 0.25, p < .001) had significant direct effects on academic motivation. Teacher–student relationship quality also significantly predicted academic motivation (β = 0.31, p < .001). Moreover, academic buoyancy (β = 0.08, p < .001) and academic conscientiousness (β = 0.07, p < .001) had significant indirect effects on academic motivation through the mediating role of teacher–student relationship quality. The total effects of academic buoyancy and conscientiousness on motivation were β = 0.37 and β = 0.32, respectively. The model demonstrated good fit with χ²/df = 2.31, CFI = 0.96, TLI = 0.95, and RMSEA = 0.056. Conclusion: The findings highlight the crucial role of both individual traits (buoyancy and conscientiousness) and relational factors (teacher–student relationships) in shaping students' academic motivation. Enhancing both psychological and interpersonal dimensions may foster sustained academic engagement and success.